2016
DOI: 10.1177/1545968316675431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Core Stability Training on Trunk Function, Standing Balance, and Mobility in Stroke Patients

Abstract: Core stability training has beneficial effects on trunk function, standing balance, and mobility in stroke patients. Our findings might provide support for introducing core stability training in stroke rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
171
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(183 citation statements)
references
References 61 publications
(103 reference statements)
2
171
0
10
Order By: Relevance
“…However, the thickening ratio of the forced expiratory muscles was not associated with total TIS score. That is, postures are induced by diaphragmatic pressure and cocontraction of the anterior and lateral abdominal muscles; thus, muscle thickness can be a crucial element of trunk balance (Saeys et al 2012;Haruyama et al 2017). The coordination of their contraction and those of adjacent muscles of the abdominal cavity reconcile respiratory, abdominal, and trunk movement (Hodges and Gandevia 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…However, the thickening ratio of the forced expiratory muscles was not associated with total TIS score. That is, postures are induced by diaphragmatic pressure and cocontraction of the anterior and lateral abdominal muscles; thus, muscle thickness can be a crucial element of trunk balance (Saeys et al 2012;Haruyama et al 2017). The coordination of their contraction and those of adjacent muscles of the abdominal cavity reconcile respiratory, abdominal, and trunk movement (Hodges and Gandevia 2000a).…”
Section: Discussionmentioning
confidence: 99%
“…Haruyama el al. [10] investigated the effects of 4 weeks of ADIM training on trunk function and standing balance in sub-acute stroke patients. The results showed that Trunk Impairment Scale, Functional Reach test, Timed Up-and-Go test, and Functional Ambulation Categories scores were significantly improved when compared to conventional neurodevelopment treatment (NDT).…”
Section: Introductionmentioning
confidence: 99%
“…This finding is of particular relevance, as recent studies have shown the positive impact of specific truncal exercises for improving trunk function, balance and mobility in patients with stroke. (9,21,22) Haruyama et al, in an assessor-blinded, randomised controlled trial of 32 participants in a stroke rehabilitation ward, showed that participants who received additional core stability training in lieu of conventional therapy had better scores on the TIS, Timed Up-and-Go test and Functional Ambulation Category. (22) This study had several limitations.…”
Section: Discussionmentioning
confidence: 99%